Star Wars Darth Vader. Vol. 2, Shadows and secrets - Gillen, Kieron (Marvel Worldwide, Inc., 2016)
Bounty Hunters on the attack--against the Empire! Vader has a new mission to do for the Empire. Unfortunately, it's completely at odds with his own mission. What's a Dark Lord to do? Plus: Who is Tagge's mysterious new agent?